2006 IEEE International Solid State Circuits Conference - Digest of Technical Papers 2006
DOI: 10.1109/isscc.2006.1696146
|View full text |Cite
|
Sign up to set email alerts
|

Printable electronics for polymer RFID applications

Abstract: Organic electronics create new opportunities of inexpensive RFID tag production techniques such as printing processes, which are only possible with soluble materials like polymers. Concepts for the production of fast integrated circuits based on p-type organic transistors have been demonstrated [1] using soluble polymers for active layer and insulating layer. A number of organic RFIDrelated building blocks and components have recently been published [2,[4][5][6][7]. This paper presents a passive organic transp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
22
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 6 publications
0
22
0
Order By: Relevance
“…In that work, lower bit generators (up to 6-bit) could be read out using a base carrier frequency of 13.56 MHz by a capacitive antenna. The ability to use organic electronics for inductively-coupled systems has been shown by Böhm et al [11], who demonstrated the read out of a ring oscillator using an inductive antenna. Ullmann field-effect transistors at 13.56 MHz [13].…”
Section: Introductionmentioning
confidence: 99%
“…In that work, lower bit generators (up to 6-bit) could be read out using a base carrier frequency of 13.56 MHz by a capacitive antenna. The ability to use organic electronics for inductively-coupled systems has been shown by Böhm et al [11], who demonstrated the read out of a ring oscillator using an inductive antenna. Ullmann field-effect transistors at 13.56 MHz [13].…”
Section: Introductionmentioning
confidence: 99%
“…Flexible and low-cost organic FETs (OFETs) are suitable for large-area electronics and have a potential as a supplement of solid and expensive silicon MOSFETs. OFETs have been applied to active-matrix displays [1]- [3], RF-ID transponders [4], [5], and sensors [6]- [10]. They are examples of the large-area electronics except for RF-ID.…”
Section: Introductionmentioning
confidence: 99%
“…Many of the targeted applications for printed organic electronics require powering either from printed batteries, [6] solar cells, [7] or via electromagnetic induction. [8] Such power sources can typically supply an entire electronic system with a voltage ranging from 1 V to only a few volts at a current often limited to less than 1 mA. Moreover, the clock frequency should be at least 100 Hz for proper operation and rapid updating of the printed electronics.…”
mentioning
confidence: 99%
“…Moreover, the clock frequency should be at least 100 Hz for proper operation and rapid updating of the printed electronics. [8] Hence, tremendous efforts are presently devoted to reducing the driving voltage of printable OTFTs simultaneously to keeping the delay time short. Figure 1 shows the lowest reported signal delay times per stage at different supply voltages (V DD ) for p-channel, [9][10][11][12][13][14][15] n-channel, [16] and complementary [17][18][19][20] OTFT circuits (ring oscillators).…”
mentioning
confidence: 99%